Using ultrafast angio planewave ultrasensitive and conventional doppler imaging techniques to assess intramuscular blood perfusion in older adults - Tiev Miller; Nonhlanhla Chambara; Michael Tin Cheung Ying; Marco Yiu Chung Pang (BMC Medical Imaging)
Abstract Background Microvascular ultrasound imaging techniques such as Angio PLanewave UltraSensitive (Angio-PL.U.S.) have been used to detect microvascular blood flow in various organs and tissues. However, the advantage of Angio-PL.U.S. for assessing muscle microvascularity over other non-invasive imaging modalities has not been investigated. This cross-sectional study compared ultrafast Angio-PL.U.S. and conventional color Doppler flow imaging (CDFI) techniques for assessing intramuscular blood perfusion. Methods Forty-five older adults participated (age = 59.1 ± 7.6). The vascularity index (VI) was used to quantify intramuscular blood flow of the bilateral biceps brachii (BB) and medial gastrocnemius (MG). Intra-limb (difference in VI between CDFI and Angio-PL.U.S. techniques) and inter-limb differences [percent side-to-side differences (%SSD) in VI between dominant and non-dominant sides] were compared using Wilcoxon Signed Ranks and Mann-Whitney U tests, respectively. Associations between techniques were assessed using Spearman’s rho (ρ). Results No significant differences were observed between dominant and non-dominant BB (p ≥ 0.053) and MG (p ≥ 0.756) for both CDFI-VI and Angio-PL.U.S.-VI. Only VI measures for the non-dominant BB demonstrated significant intra-limb difference between techniques (p = 0.002). A significant %SSD between techniques was observed for BB (p = 0.022) but not MG (p = 0.225). Strong to very strong correlations were observed between CDFI-VI and Angio-PL.U.S.-VI across all muscles (ρ = 0.616–0.814, p ≤ 0.001). Conclusion Ultrafast Angio-PL.U.S. and conventional ultrasound imaging techniques were comparable when used in conjunction with the VI for quantifying resting intramuscular blood flow. Angio-PL.U.S. appeared to be more sensitive in detecting bilateral disparities in upper extremity muscles. However, further research is needed to validate these findings and investigate the potential clinical utility of this technique for characterizing disease progression in populations with global or unilateral musculoskeletal tissue alterations.